Fiscal policy events and interest rate swap spreads: evidence from the EU - Afonso, António (2010)
In this paper we assess the importance given in capital markets to the credibility of the European fiscal framework. We evaluate to which extent relevant fiscal policy events taking place in the course of 2002 produced a reaction in the long-term bond segment of the capital markets. Firstly, we identify the fiscal policy events and qualitatively assess the views of capital market participants. Secondly, we estimate the impact of these fiscal events on the interest rate swap spreads, which is our measure for the risk premium. According to our results the reaction of swap spreads, where it turned out to be significant, has been mostly around five basis points or less.